(untitled) (Годишник на УНСС, 2023)
The brand is an element that signals the quality of the product. The credibility of brands is generally developed through considerable efforts by individual firms and is often based on consumers’ personal experiences over time. By using trusted labels, firms signal to the consumer the quality or presence of specific attributes. Brand image has a significant impact on brand equity, which refers to the consumer’s overall perception and feeling about a particular brand and influences consumer behavior. Consumers are always looking for famous brands, so their preferences for the brand of a product or service are variable. Businesses need to identify what influences brand preference and how consumers create brand preference.Often customers, when they are satisfied with a particular product or brand, repeatedly buy the product. When a customer repeatedly buys a product, showing a favorable attitude towards the brand, the customer becomes loyal. To make consumers buy or prefer a brand, they must first be made aware of the brand and focus on maintaining and monitoring brand awareness. So there is an immediate need for a marketer to know the olive oil brand consumers’ preferences and identify what affects their brand preference. Various factors influence consumer preferences for olive oil brands. This study aims to analyze how consumer knowledge of olive oil brands affects branded olive oil and the willingness to pay for branded olive oil. In this study we identify relevant literature review on consumer preferences for food products and consumer preferences for olive oil. The focuses of this research are only Albanian olive oil brands. The subjects of the research are Albanian consumer preferences for branded olive oil. The study object includes Albanian individual consumers at the age 18 + that take care of buying olive oil products. Data are collected from an online questionnaire, and the association between variables will be tested using statistical tests.